2021
DOI: 10.1371/journal.pone.0254842
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal canine cortisol measurement in multiple matrices during the perinatal period: A pilot study

Abstract: Stress exposure during perinatal period may lead to maternal cortisol increase that negatively affects the offspring development. In recent years, the interest on non-invasive sampling methods to measure cortisol as a marker of stress is increasing in both humans and animals. Indeed, discomfort due to blood collection may compromise the diagnostic outcome, mainly in uncooperative patients. So far, some alternative matrices but not milk have been explored in adult dogs, while no data are available on the neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…In humans, e.g., fetal glucocorticoids are 5-10 times lower than maternal circulatory levels [59]. Although several studies have attempted to measure fetal exposition to cortisol in the dog using, e.g., puppy hair and claws [60,61], a clear comparison with maternal levels is still not available. Nevertheless, it appears plausible that such a protective mechanism might be also present in the dog.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, e.g., fetal glucocorticoids are 5-10 times lower than maternal circulatory levels [59]. Although several studies have attempted to measure fetal exposition to cortisol in the dog using, e.g., puppy hair and claws [60,61], a clear comparison with maternal levels is still not available. Nevertheless, it appears plausible that such a protective mechanism might be also present in the dog.…”
Section: Discussionmentioning
confidence: 99%
“…Although a different species, our finding is supported by a recent study in cats, which observed higher concentrations of serum cortisol at 4 weeks postpartum than before mating, 1–2 days after parturition and 8 weeks postpartum [ 36 ]. In contrast, more recent studies in dogs found no change in coat and claw cortisol between 4 and 8 weeks postpartum [ 29 ], or plasma and salivary cortisol between parturition, 21, and 60 days postpartum [ 28 ]. The difference in findings may be due to the larger sample size and representation of multiple breeds in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…We collected data from a minimum of six dams per kennel to ensure adequate representation of within kennel variation. The total number of kennels included in the study ensured a representation of different environments and management practices and allowed us to reach a sample size larger than other similar research in different populations [ 28 , 29 , 36 ]. To maximize data collection time and travel, each kennel was required to have a minimum of three bitches that met selection criteria and were expected to whelp in the same week.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation